There is still a long way to go: An exploratory study on the factors contributing to the inclusion and exclusion of female character representation in video games - Lybe,Erika; Rufrancos Luna,Arantxa (2023)
Thesis Purpose: This thesis aims to explore the complex phenomenon of female character representation, both quantity and portrayal, in video games and which factors either inhibit or enhance the creation and how. Methodology: A qualitative study with an inductive approach, designed to answer the research question “How do different factors contribute to the inclusion or exclusion of female character representation in video games?”. Theoretical Perspective: In order to address the research question, an extensive review of the literature is conducted, drawing upon market orientation, female video game characters and product development theory. Specifically for the later, the influence of organisational structure, risk behaviour and workforce on decision-making within the product development process is discussed. Empirical data: The gathered data consisted of 11 in-depth semi-structured interviews with industry experts. Findings & conclusion: The research discovered that market forces, video game storylines, organisational structure, risk behaviour, team diversity, and top management support simultaneously function as barriers or enablers in the representation of female characters in video games –depending on their interplay. Namely, these factors exhibit a dual role; thus, their impact on female character representation is not fixed but changes with regard to the interactions among all other identified factors. Furthermore, not all factors are equally weighted, some have a bigger influence than others.
Keywords: Inclusion; Diversity; Video Games; Female characters; Representation